The effects on some non-enzymatic antioxidants and oxidative stress of Astacus leptodactylus (Esch., 1823) of starvation periods - Barim-Oz, Ozden (Wiley, 2018)
This study investigated the effect of starvation (78days) and refeeding (33days) on the oxidative stress [malondialdehyde (MDA)] and the non-enzymatic antioxidants [vitamin E (VE), vitamin C (VC), vitamin A (VA), beta carotene (C) and reduced glutathione (GSH)] in the hepatopancreas, muscle and gill tissues of freshwater crayfish (Astacus leptodactylus). Crayfish were divided into three experimental groups: control (fed), starved (not fed) crayfish for 78days and refeeding crayfish for 33days after 78days of starvation. The biochemical analysis of the tissues was conducted at 3, 18, 33, 48, 63 and 78days of starvation and feeding and at 3, 18 and 33days of refeeding. It was determined that crayfish can withstand starvation period of 78days. In all of the periods, the MDA levels were significantly higher in the tissues of starved crayfish when compared with the control. The findings of this study demonstrate that starvation has a negative effect on the VE, VC, VA, C and GSH levels in the crayfish. The measured parameters returned to control values after 33days of the refeeding. Additionally, the starvation resulted in decreased levels of VE, VA and C in the abdomen muscle of crayfish consumed by humans.
Keywords: crayfish; glutathione; oxidative stress; starvation; vitamins